On Matching Book: A Problem in Banking and Corporate Finance - Shubik, M.; Sobel, M. J. (Management Science, 1992)
In each of the asset and liability markets in which the banking firm is an intermediary, typically there are instruments with differing maturities. The bank matching book problem is to manage the term structures of assets and liabilities. In our first model, the bank borrows and lends only short run. In our second model, the bank borrows only short run but can lend short run and long run. The criterion in both models is the expected value of the present value of dividends issued. Both models yield dynamic programming problems. Broad aspects of optimal policies are indicated.